The paradox of Zeno in bariatric surgery weight loss: Superobese patients run faster than morbidly obese patients, but can't overtake them - Medas, Fabio; Moroni, Enrico; Deidda, Simona; Zorcolo, Luigi; Restivo, Angelo; Canu, Gian Luigi; Cappellacci, Federico; Calò, Pietro Giorgio; Pintus, Stefano; Fantola, Giovanni (Frontiers in Surgery, 2023)
Superobesity (SO) is defined as a BMI>50 Kg/m2, and represents the extreme severity of the disease, resulting in a challenge for the surgeons. In this retrospective study we aimed to compare the outcomes of SO patients compared to morbidly obese (MO) patients. We included in this study 154 MO patients, with a median preoperative BMI of 40.8 kg/m2, and 19 SO patients with median preoperative BMI of 54.9 kg/m2. The MO patients underwent sleeve gastrectomy (SG) in 62 (40.3%) cases, laparoscopic Roux-and-Y gastric bypass (LRYGBP) in 85 (55.2%) cases and One-Anastomosis Gastric Bypass (OAGB) in 7 (4.5%) cases. underwent OAGB. The patients in the SO group were submitted to SG in 11 (57.9%) cases, LRYGBP in 5 (26.3%) cases, and OAGB in 3 (15.8%). At 24-month follow-up, an excess weight loss (EWL) >50% was achieved in 129 (83.8%) patients in the MO group and in 15 (78.9%) in the SO group (p = 0.53). A BMI<35 kg/m2 was achieved in 137 (89%) patients in the MO group and from 8 (42.2%) patients in the SO group (p <0.001). The total weight loss was significantly directly related to the initial BMI. Superobesity was identified as independent risk factor for surgical failure when considering the outcome of BMI < 35 kg/m2. Our study confirms that, although SO patients tend to gain a greater weight loss than MO patients, they less frequently achieve the desired BMI target. In this setting, it should be necessary to re-consider malabsorptive procedures as first choice.